2019
DOI: 10.1002/ece3.5100
|View full text |Cite
|
Sign up to set email alerts
|

The harmful algae, Cochlodinium polykrikoides and Aureococcus anophagefferens, elicit stronger transcriptomic and mortality response in larval bivalves (Argopecten irradians) than climate change stressors

Abstract: Global ocean change threatens marine life, yet a mechanistic understanding of how organisms are affected by specific stressors is poorly understood. Here, we identify and compare the unique and common transcriptomic responses of an organism experiencing widespread fisheries declines, Argopecten irradians (bay scallop) exposed to multiple stressors including high p CO 2 , elevated temperature, and two species of harmful algae, Coch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 101 publications
0
5
0
Order By: Relevance
“…Briefly, the experiment started with four biologically independent replicates (replicated culture tanks), however, we have used only three of these replicates for transcriptomic analysis. This pooling of samples was done with purpose, i.e., to reduce biological variability between replicate samples obtained from multiple parents and to deduct the treatment effect without baseline variation (Dineshram et al, 2015(Dineshram et al, , 2016Griffith et al, 2019). RNA concentration and integrity were measured by NanoDrop (Thermo Fisher Scientific) and Agilent 2100 BioAnalyzer (Agilent Technologies), respectively.…”
Section: Rna Extractionmentioning
confidence: 99%
“…Briefly, the experiment started with four biologically independent replicates (replicated culture tanks), however, we have used only three of these replicates for transcriptomic analysis. This pooling of samples was done with purpose, i.e., to reduce biological variability between replicate samples obtained from multiple parents and to deduct the treatment effect without baseline variation (Dineshram et al, 2015(Dineshram et al, , 2016Griffith et al, 2019). RNA concentration and integrity were measured by NanoDrop (Thermo Fisher Scientific) and Agilent 2100 BioAnalyzer (Agilent Technologies), respectively.…”
Section: Rna Extractionmentioning
confidence: 99%
“…The effect of climate change on larval development was studied using a transcriptomic approach [ 44 , 45 , 46 ]. The experiment showed that ocean acidification suppressed the immune response pathways of pacific oyster Crassostrea gigas larvae [ 93 ].…”
Section: Transcriptomicsmentioning
confidence: 99%
“…HABs, including M. polykrikoides, have led to the collapse of some bivalve fisheries (Bricelj and Kuenstner, 1989) and can affect bivalves in different ways depending on the bivalve species and life stage (Gobler et al, 2008;Tang and Gobler, 2009b;Griffith et al, 2019b;Griffith et al, 2019c). Some adult bivalves can experience mortality or possible gonadal depression when exposed to HABs (Bricelj et al, 2005) and accumulate high levels of toxins (Zingone and Enevoldsen, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Some adult bivalves can experience mortality or possible gonadal depression when exposed to HABs (Bricelj et al, 2005) and accumulate high levels of toxins (Zingone and Enevoldsen, 2000). Compared to their adult counterparts, larval and juvenile bivalves are typically more susceptible to HABs (Gobler et al, 2008;Tang and Gobler, 2009b;Li et al, 2012;Griffith et al, 2019b). M. polykrikoides in particular can be highly toxic and lethal to early life stage bivalves and have been shown to cause mortality in larval and juvenile Crassostrea virginica (eastern oyster) and Argopecten irradians (bay scallop) (Gobler et al, 2008;Tang and Gobler, 2009b;Li et al, 2012;Griffith et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation